2019
DOI: 10.1016/j.watres.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CDOM in saline and freshwater lakes across China using spectroscopic analysis

Abstract: China were examined to determine relationships between lake water sources (fresh versus saline) and their fluorescence/absorption characteristics. Results indicated significant differences regarding DOC concentration and a CDOM (254) between freshwater (6.68 mg C L-1 , 19.55 m-1) and saline lakes (27.4 mg C L-1 , 41.17 m-1). While humic-like (F 5) and fulvic-like (F 3) compounds contributed to CDOM fluorescence in all lake waters significantly, their contribution to total fluorescence intensity (F T) differed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(55 citation statements)
references
References 59 publications
6
49
0
Order By: Relevance
“…In this study, the absorption coefficient of CDOM at 254 nm (α 254 , m −1 ) was used as a proxy for CDOM concentration. The value of α 254 was determined using the following equation [24]:…”
Section: Chromophoric Dom Absorption Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, the absorption coefficient of CDOM at 254 nm (α 254 , m −1 ) was used as a proxy for CDOM concentration. The value of α 254 was determined using the following equation [24]:…”
Section: Chromophoric Dom Absorption Analysismentioning
confidence: 99%
“…CDOM is part of the DOM and is involved in the absorption of UV and photosynthetically available radiation [29][30][31]. CDOM is a major component of DOM in water and plays a vital role in carbon cycling in inland water [24,32]. The CDOM concentration, represented by α 254 in the overlying water of Lake Hulun, ranged from 6.97 m −1 to 86.89 m −1 , and showed significant seasonal differences.…”
Section: Spatial and Temporal Distribution Characteristics Of Cdommentioning
confidence: 99%
See 2 more Smart Citations
“…Conmy et al [29] found changes in the CDOM absorption spectral slope S 280−312 with salinity to be a result of mixing of CDOM originating from freshwater and marine humics together with photo-bleaching in coastal water. Song et al [34] discovered that the humic-like materials in CDOM tended to decrease with altitude in lakes.…”
Section: Introductionmentioning
confidence: 99%